Pengembangan Alat Percobaan dan Lembar Kerja Peserta Didik (LKPD) Berbasis STEM pada Materi Gelombang Bunyi (Kelintang Jolo) - Devi Harmita; Haerul Pathoni; Budi Eka Dharma (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to Develop experimental tools and STEM-based Student Worksheets (LKPD) on sound wave material using Arduino technology and Kelintang Jolo local wisdom for eleventh-grade high school students in Jambi Province. The 4D Development model (Define, Design, Develop, Disseminate) was employed, limited to the Develop stage. Validation involved three validators using Aiken's V formula, while practicality was measured through student response questionnaires analyzed descriptively. Results showed content validity reaching V-Aiken 0.75 (Valid) and media validity 0.72 (Valid) at Stage II. Practicality testing on 30 students at SMA Negeri 8 Jambi City yielded a mean response score of 3.19 out of 4 (Good/Practical) with Cronbach's Alpha 0.86 (Reliable). The Kelintang Jolo context and Arduino technology integration successfully enhanced the relevance and appeal of sound wave learning material. The product is declared valid and practical as an innovative physics learning medium integrating local wisdom with 21st-century technology.